Assessing the Extent of Environmental Risks From Nickel in European Freshwaters: A Critical Reflection of the European Commission's Current Approach. (5th June 2022) - Peters, Adam; Wilson, Iain; Merrington, Graham; Schlekat, Christian; Middleton, Ellie; Garman, Emily
Abstract: Nickel (Ni) has a been a Priority Substance under the European Water Framework Directive since 2008. As such it is deemed to present an European Union‐wide risk to surface waters. Since 2013, the Ni Environmental Quality Standard (EQS) has been bioavailability‐based, and new European Guidance supports accounting for bioavailability in assessing Ni compliance with the EQS. The European Commission has developed an approach to determine whether Priority Substances present a sufficient European Union‐wide risk to justify an ongoing statutory monitoring programme, effectively to deselect a substance. This is a key step to ensure that finite monitoring resources are targeted at delivering environmental benefit, when there is an ever‐growing burden of determinands to measure for all regulators. When the European Commission performed this exercise for Ni without accounting for bioavailability, they concluded that Ni should not be deselected, and Ni is an European Union‐wide risk. Performing this same exercise with the same methodology, using regulatory monitoring data for over 300 000 samples, from more than 19 000 sites across Europe, and accounting for bioavailability, as detailed in the Directive, >99% of sites comply with the Ni EQS. Nickel shows very low risks for all of the criteria identified by the European Commission that need to be met for deselection. Accounting for bioavailability is key in the assessment of Ni risks in surface waters to deliver ecologically relevant outcomes. Environ Toxicol Chem 2022;41:1604–1612. © 2022 NiPERA. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.